2020
DOI: 10.14515/monitoring.2020.6.1778
|View full text |Cite
|
Sign up to set email alerts
|

Пути российской инфодемии: от WhatsApp до Следственного комитета

Abstract: С января 2020 г. авторы статьи в составе научной группы «Мониторинг актуального фольклора» изучали в России особенности инфодемии — волны слухов, псевдомедицинских советов, конспирологии и отрицания опасности, связанных с эпидемией COVID-19. Цель исследования заключалась в характеристике структуры и путей распространения инфодемии, а для ее реализации были составлены две базы данных: (1) отобранные с помощью сервиса «Медиалогия» тексты из российских социальных сетей (167 сюжетов) и (2) случаи уголовного и адми… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For example, 'Operation InfeKtion' was used to spread disinformation around the world that the United States government created the HIV epidemic (Grimes, 2017), and Russian trolls have contributed to amplifying and politicising the vaccine debate and spreading disinformation about the measles vaccine via Twitter (Broniatowski et al, 2018). Researchers found that the largest group of people contributing to the infodemic on Russian social media is 'COVID-dissidents' or those claiming that the threat of the virus is being exaggerated and the government is using it to promote their own interests (Arkhipova et al, 2020). Arkhipova et al (2020) postulate that social media use for information about COVID-19 is so high in Russia because when there is such low-levels of trust of institutions and official sources of information, people prefer to receive the information via horizontal channels.…”
Section: Government Control Over Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 'Operation InfeKtion' was used to spread disinformation around the world that the United States government created the HIV epidemic (Grimes, 2017), and Russian trolls have contributed to amplifying and politicising the vaccine debate and spreading disinformation about the measles vaccine via Twitter (Broniatowski et al, 2018). Researchers found that the largest group of people contributing to the infodemic on Russian social media is 'COVID-dissidents' or those claiming that the threat of the virus is being exaggerated and the government is using it to promote their own interests (Arkhipova et al, 2020). Arkhipova et al (2020) postulate that social media use for information about COVID-19 is so high in Russia because when there is such low-levels of trust of institutions and official sources of information, people prefer to receive the information via horizontal channels.…”
Section: Government Control Over Informationmentioning
confidence: 99%
“…Researchers found that the largest group of people contributing to the infodemic on Russian social media is 'COVID-dissidents' or those claiming that the threat of the virus is being exaggerated and the government is using it to promote their own interests (Arkhipova et al, 2020). Arkhipova et al (2020) postulate that social media use for information about COVID-19 is so high in Russia because when there is such low-levels of trust of institutions and official sources of information, people prefer to receive the information via horizontal channels. Social media and the internet have changed how the Russian government controls information and the media narrative, and caused the state to 'rewire its propaganda' (Oates, 2016).…”
Section: Government Control Over Informationmentioning
confidence: 99%